The Impact of Covid-19 Outbreak Towards UUM Student Mobility Programme (S/O 14917) - Anuar, Nur Khairiel (UUM, 2023)
The COVID-19 pandemic crisis has changed the digital revolution to replace the normal face-to-face practice and it has a strong impact rather strengthen the university new norm. The measures and policies of international students’ movement required for a revised and confirmation with the government operation procedures. Mobility programme also had disrupted and become less attractive due to new experience learning virtually. In short, virtual mobility or cross-border education are offered rapidly due to pandemic situation. Without travelling to cross-border, virtual mobility offers same advantages as physical mobility using information and communication technologies. This research is expected to find answers for a few objectives i.e., (i) to analyse key factors that may influence students’ participation during COVID-19; (ii) to evaluate the students’ perceptions on mobility programme during COVID-19; and (iii) to recommend a mobility programme guideline implementation during crisis. This research is an exploratory study with a mixed-method approach via interview and survey. The sample which is randomly selected is among students who enrolled in the mobility programme i.e., inbound and outbound. It is expected to give an overview of the factors that affected students to engage in the mobility programme during the pandemic via the perceptions gathered which could assist university in future mobility engagement. Hence, accordingly, a suitable strategy could be developed to engage in mobility programme during a pandemic crisis.